negative 3...............................
Answer:
0.216 = 0.6³
Step-by-step explanation:
using the rule of logarithms
•
x = n ⇔ x = ![b^{n}](https://tex.z-dn.net/?f=b%5E%7Bn%7D)
0.216 = 3 ⇒ 0.216 = ![0.6^{3}](https://tex.z-dn.net/?f=0.6%5E%7B3%7D)
Answer:
No sorry I don't
I did that last year and I don't remember how
Step-by-step explanation:
Using compound interest, the rates per compounding period are given as follows:
a) 0.1273 = 12.73%.
b) 0.0833 = 8.33%
c) 0.0617 = 6.17%
<h3>What is compound interest?</h3>
The amount of money earned, in compound interest, after t years, is given by:
![A(t) = P\left(1 + \frac{r}{n}\right)^{nt}](https://tex.z-dn.net/?f=A%28t%29%20%3D%20P%5Cleft%281%20%2B%20%5Cfrac%7Br%7D%7Bn%7D%5Cright%29%5E%7Bnt%7D)
In which:
- A(t) is the amount of money after t years.
- P is the principal(the initial sum of money).
- r is the interest rate(as a decimal value).
- n is the number of times that interest is compounded per year.
The <u>interest rate per compounding period</u> is given as follows:
![\left(1 + \frac{r}{n}\right)^n - 1](https://tex.z-dn.net/?f=%5Cleft%281%20%2B%20%5Cfrac%7Br%7D%7Bn%7D%5Cright%29%5En%20-%201)
For item a, the parameters are:
r = 0.12, n = 52.
Hence:
![\left(1 + \frac{0.12}{52}\right)^{52} - 1 = 0.1273](https://tex.z-dn.net/?f=%5Cleft%281%20%2B%20%5Cfrac%7B0.12%7D%7B52%7D%5Cright%29%5E%7B52%7D%20-%201%20%3D%200.1273)
For item b, the parameters are:
r = 0.08, n = 104.
Hence:
![\left(1 + \frac{0.08}{104}\right)^{104} - 1 = 0.0833](https://tex.z-dn.net/?f=%5Cleft%281%20%2B%20%5Cfrac%7B0.08%7D%7B104%7D%5Cright%29%5E%7B104%7D%20-%201%20%3D%200.0833)
For item c, the parameters are:
r = 0.06, n = 12.
Hence:
![\left(1 + \frac{0.06}{12}\right)^{12} - 1 = 0.0617](https://tex.z-dn.net/?f=%5Cleft%281%20%2B%20%5Cfrac%7B0.06%7D%7B12%7D%5Cright%29%5E%7B12%7D%20-%201%20%3D%200.0617)
More can be learned about compound interest at brainly.com/question/25781328
#SPJ1
I suppose the integral could be
![\displaystyle\int_7^\infty\frac{e^{-1/x}}{x^2}\,\mathrm dx](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_7%5E%5Cinfty%5Cfrac%7Be%5E%7B-1%2Fx%7D%7D%7Bx%5E2%7D%5C%2C%5Cmathrm%20dx)
In that case, since
as
, we know
. We also have
, so the integral is approach +1 from below. This tells us that, by comparison,
![\displaystyle\frac{e^{-1/x}}{x^2}\le\frac1{x^2}\implies\int_7^\infty\frac{e^{-1/x}}{x^2}\,\mathrm dx\le\int_7^\infty\frac{\mathrm dx}{x^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac%7Be%5E%7B-1%2Fx%7D%7D%7Bx%5E2%7D%5Cle%5Cfrac1%7Bx%5E2%7D%5Cimplies%5Cint_7%5E%5Cinfty%5Cfrac%7Be%5E%7B-1%2Fx%7D%7D%7Bx%5E2%7D%5C%2C%5Cmathrm%20dx%5Cle%5Cint_7%5E%5Cinfty%5Cfrac%7B%5Cmathrm%20dx%7D%7Bx%5E2%7D)
and the latter integral is convergent, so this integral must converge.
To find its value, let
, so that
. Then the integral is equal to
![\displaystyle\int_{-1/7}^0e^u\,\mathrm du=e^0-e^{-1/7}=1-\frac1{\sqrt[7]{e}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_%7B-1%2F7%7D%5E0e%5Eu%5C%2C%5Cmathrm%20du%3De%5E0-e%5E%7B-1%2F7%7D%3D1-%5Cfrac1%7B%5Csqrt%5B7%5D%7Be%7D%7D)